An analysis of auction strategies in apartment sales. Issue 2 (6th August 2018) - Hungria-Gunnelin, Rosane
Abstract : Purpose: This paper aims to empirically test the effect of list price and bidding strategies in ascending auctions of residential real estate. Design/methodology/approach: Three regression models are estimated, using a unique data set from 629 condominium apartments in the inner-city of Stockholm, Sweden, sold between January 2010 and December 2011. Findings: The results show that jump bidding has the predicted effect of reducing competition by scaring off bidders. However, a higher average bid increment leads to a higher selling price. Furthermore, results show that a fast auction in terms of average time between bids acts to increase the probability of so-called auction fever as both the number of bidders and the selling price are positively correlated with the speed of the auction. While the average behavior of all auction participants, in terms of jump bidding and time between bids, significantly affects auction outcomes, differences in strategies applied by winners and losers show mixed results. The results of this study with respect to sellers' list price strategy show that underpricing is an ineffective strategy in terms of enticing more bidders to participate in the auction. Furthermore, underpricing is not sufficient to have a positive effect on the selling price. Originality/value: This paper is one of the first papers to empirically analyze how different bidding strategies affect the outcome of residential real estate auctions in terms of competition and the final selling price.